Effect of Subtitution of Texturized Vegetable Protein Using Tempeh Towards Nutrional and Textural Quality Of Plant-Based Nuggets - Indriani, Widya; Crespo, Ivan; Dewi, Desak Putu Ariska Pradnya; Insani, Rayyane Mazaya Syifa (Indonesian Journal of Life Sciences, 2022)
The development of Plant-based Meat Alternatives (PBMAs) has been focused on mimicking the textural, taste, appearance, aroma, and nutritional properties of real meat products. Texturized Vegetable Protein (TVP) has been widely used in food applications to construct plant-based meat products. However, the high energy cost to produce TVP leaves the price of TVP quite expensive. Therefore, this experiment aims to see the effect of tempeh as an alternative to TVP on the nutritional and textural properties of plant-based nuggets (PBNs). In total, five PBN treatments were analyzed and compared to chicken nuggets for their nutritional and textural properties. The treatments were 1) C1: control (hung + ground TVP), 2) Hung TVP and tempeh (HT), 3) Ground TVP and tempeh (GT), 4) Tempeh only (TT), and 5) Hung TVP, ground TVP, and tempeh (HGT). From the results, all plant-based nugget treatments had significantly higher (p<0.05) protein and moisture content and lower fat content than commercial chicken nuggets. Whereas for textural properties, except C1 and HGT, all other PBN treatments had poorer hardness than commercial chicken nuggets. Overall, the addition or substitution of tempeh on hung and ground TVP treated PBN did not affect the protein, fat, and moisture content of PBNs, but significantly produced better nutritional properties than chicken nugget. In terms of textural properties, combination of Hung TVP, ground TVP, and tempeh provide the desirable textural properties as it can be comparable to chicken nuggets.